Ethylene glycol poisoning treated using combination of ethanol and haemodialysis therapy instead of fomepizole: a case report - Une, Kazunobu; Kishi, Yasumasa; Hidaka, Yui; Esaki, Takashi (International Journal of Medicine, 2021)
We report a case of ethylene glycol poisoning in a 70-year-old man with headache and dysarthria. Blood tests showed a marked increase in the anion gap (29.8 mOsm/kg) and osmotic gap (14 mOsm/kg). The estimated blood concentration of ethylene glycol was 86.8 mg/dL. Ethanol was administered and he underwent haemodialysis for 7 cycles, which was discontinued on day 12. Fomepizole, which competes with alcohol dehydrogenase, is an effective treatment for ethylene glycol poisoning. However, it is usually prescribed within 24 h after poisoning, and studies on its use in cases of severe acute renal injury over time are limited. We were able to obtain good results with haemodialysis without using fomepizole. Conventional treatments such as haemodialysis may be more useful than fomepizole in terms of cost benefits in patients with addiction who have been taking the drug for a long time or who have advanced renal injury.Â Â Â